Pengembangan E - Modul Berbasis Model Pembelajaran Game Based Learning (GBL) Pada Pembelajaran Bahasa Indonesia Materi Teks Prosedur Kelas VII MTSN 1 Tebo - Lala Pitalia; Deviani Putri; Rama Fitria; Rendi Marlianda (Dharmas Education Journal (DE_Journal), 2024)
This study aims to develop an e-module based on the Game-Based Learning (GBL) model for Indonesian language instruction, specifically on procedural text material for seventh-grade students at MTs Negeri 1 Tebo. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The needs analysis revealed that students were bored with monotonous learning methods and preferred fun, game-based approaches. Based on these findings, the researcher developed an interactive GBL-based e-module using Canva and converted it into a digital flipbook format. The developed e-module was validated by three experts—subject matter, media, and language experts—with an average score of 88%, categorized as very valid. Practicality was assessed through questionnaires distributed to teachers and students, yielding scores of 82% and 91.8% respectively, both categorized as very practical. Effectiveness was evaluated through post-tests, showing that 85,51% of students achieved the minimum mastery criteria, indicating that the e-module is highly effective for learning. In conclusion, the GBL-based e-module developed in this study is valid, practical, and effective for use as instructional material in Indonesian language learning, particularly for procedural text topics.